The answer is the transitive property
Answer:
yes it is true becasue ya so that equals and that is why 5(4 − x) < 3x + 1
Step-by-step explanation:
Hello!
Simplifying
5x2 + -7x + -3 = 8
Reorder the terms:
-3 + -7x + 5x2 = 8
Solving
-3 + -7x + 5x2 = 8
Solving for variable 'x'.
Reorder the terms:
-3 + -8 + -7x + 5x2 = 8 + -8
Combine like terms: -3 + -8 = -11
-11 + -7x + 5x2 = 8 + -8
Combine like terms: 8 + -8 = 0
-11 + -7x + 5x2 = 0
Begin completing the square. Divide all terms by
5 the coefficient of the squared term:
Divide each side by '5'.
-2.2 + -1.4x + x2 = 0
Move the constant term to the right:
Add '2.2' to each side of the equation.
-2.2 + -1.4x + 2.2 + x2 = 0 + 2.2
Reorder the terms:
-2.2 + 2.2 + -1.4x + x2 = 0 + 2.2
Combine like terms: -2.2 + 2.2 = 0.0
0.0 + -1.4x + x2 = 0 + 2.2
-1.4x + x2 = 0 + 2.2
Combine like terms: 0 + 2.2 = 2.2
-1.4x + x2 = 2.2
The x term is -1.4x. Take half its coefficient (-0.7).
Square it (0.49) and add it to both sides.
Add '0.49' to each side of the equation.
-1.4x + 0.49 + x2 = 2.2 + 0.49
Reorder the terms:
0.49 + -1.4x + x2 = 2.2 + 0.49
Combine like terms: 2.2 + 0.49 = 2.69
0.49 + -1.4x + x2 = 2.69
Factor a perfect square on the left side:
(x + -0.7)(x + -0.7) = 2.69
Calculate the square root of the right side: 1.640121947
Break this problem into two subproblems by setting
(x + -0.7) equal to 1.640121947 and -1.640121947.
Subproblem 1
x + -0.7 = 1.640121947
Simplifying
x + -0.7 = 1.640121947
Reorder the terms:
-0.7 + x = 1.640121947
Solving
-0.7 + x = 1.640121947
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '0.7' to each side of the equation.
-0.7 + 0.7 + x = 1.640121947 + 0.7
Combine like terms: -0.7 + 0.7 = 0.0
0.0 + x = 1.640121947 + 0.7
x = 1.640121947 + 0.7
Combine like terms: 1.640121947 + 0.7 = 2.340121947
x = 2.340121947
Simplifying
x = 2.340121947
Subproblem 2
x + -0.7 = -1.640121947
Simplifying
x + -0.7 = -1.640121947
Reorder the terms:
-0.7 + x = -1.640121947
Solving
-0.7 + x = -1.640121947
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '0.7' to each side of the equation.
-0.7 + 0.7 + x = -1.640121947 + 0.7
Combine like terms: -0.7 + 0.7 = 0.0
0.0 + x = -1.640121947 + 0.7
x = -1.640121947 + 0.7
Combine like terms: -1.640121947 + 0.7 = -0.940121947
x = -0.940121947
Simplifying
x = -0.940121947
Solution
The solution to the problem is based on the solutions
from the subproblems.
x = {2.340121947, -0.940121947}
The number of minutes for which Keith was billed = 97
Step-by-step explanation:
Step 1:
It is given that Keith pays a fixed fee of 3$ a month and 11 cents per minute for the number of minutes used.
Total cost = Fixed cost + Per minute cost
If x represents the number of minutes consumed in a month then we can compute the total cost using the below equation:
Total cost = 3$ + 0.11 * x
Step 2:
The total cost is 13.67$
Substituting in the equation we get
13.67 = 3 + 0.11 * x
x = 10.67 / 0.11 = 97 minutes
Step 3:
Answer:
The number of minutes for which Keith was billed = 97